Deixis Places in Online Shopping Advertising - Siti Musarrofah (JELITA, 2022)
Advertising in online shopping serves as a means to promote or advertise an item or service in the hope of obtaining maximum income of the advertised product. Usually an advertisement uses languages ​​that are very short, concise, clear and interesting to influence the public and the general public. This study aims to identify the form of place deixis found in online shopping advertisements. The method used in this research is descriptive qualitative method. The data in this study are in the form of clauses, sentences, and discourses containing place deixis in online shopping advertisements. The data collection techniques used in the research are listen and note technique. Meanwhile, data analysis includes (1) classifying advertising data online shopping; (2) classifying the place deixis form data; and (3) set aside data that similar but not the same based on the form of clauses, sentences, and discourses. The results of this study shows that the form of place deixis in online shopping advertisements with data of 5 data in the form of clauses, sentences, and discourses.